Kematangan Vokasional Dengan Kecemasan Menghadapi Dunia Kerja Pada Siswa SMK X Kabupaten Solok - Kurniawan, Hari; Titisemita, Ane; Putra, Ovan Zulia (LPPM Universitas Dharma Andalas, 2024)
This study aims to determine the relationship between vocational maturity and anxiety in facing the world of work in students of SMK Negeri 2 Gunung Talang. The independent variable in this study is vocational maturity while the dependent variable is anxiety in facing the world of work. The measuring tool used in this study is the vocational maturity scale and anxiety in facing the world of work. The sampling technique in this study used a proportionate stratified random sampling technique. The sample in this study were 133 students of SMK Negeri 2 Gunung Talang. Test the validity and reliability in this study using Alpha Cronbach technique. The results of the validity coefficient on the vocational maturity scale move from rix = 0.319 to rix = 0.771 with a reliability coefficient value of α = 0.945 while the results of the validity coefficient on the anxiety scale in facing the world of work move from rix = 0.329 to rix = 0.746 with a reliability coefficient value of α = 0.939. Based on data analysis, a correlation value of -0.522 was obtained with a significance level of 0.000, which means that the hypothesis is accepted. This shows that there is a significant relationship between vocational maturity and anxiety in facing the world of work in students of SMK Negeri 2 Gunung Talang.